Fear of COVID-19 among cancer patients in Henan Province, Central China: causes, results, and coping factors - Mao, Yiqing; Ma, Wenjie; Kang, Dingding; Miao, Yudong; Fu, Hang; Zhang, Bowen; Zhang, Jiangong; Wu, Jian (Frontiers in Psychology, 2023)
Objectives: This study aims to examine the fear level of COVID-19 among cancer patients in Henan Province, Central China and to identify its causes, results, and coping factors. Methods: An online survey was conducted among 1,067 cancer patients. The participants reported their individual fear level of COVID-19, risk of COVID-19 infection, risk of death from COVID-19, COVID-19 vaccination concerns, influence level of COVID-19 pandemic on their disease treatment, loneliness due to COVID-19, economic burden from COVID-19, quality of life, safety behavior, information regarding COVID-19 vaccination, psychological guidance, physical activities, and demographic characteristics. Chi-square and cumulative logistic regression were used to determine the predictors of COVID-19 fear level. Results: This study indicates that cancer patients report moderate fear level of COVID-19 in Central China (66.9%). The six cause factors (risk of COVID-19 infection, risk of death from COVID-19, COVID-19 vaccination concerns, influence level of COVID-19 pandemic on disease treatment, loneliness due to COVID-19, and economic burden from COVID-19) were positively associated with COVID-19 fear level. Three coping factors (information regarding COVID-19 vaccination, psychological guidance, and physical activities) were negatively associated with COVID-19 fear level. COVID-19 fear level was negatively associated with quality of life and positively associated with safety behavior. Conclusions: Our results suggest that governments should improve access to personalized vaccine counseling and psychological guidance by undertaking the responsibility of patients’ attending physicians and increasing publicity. Physical activities should be included in the treatment program to help cancer patients better recover their physical and mental health.